Halal concept best practice for food space design in Klang valley / Nor Hazirah Hasri - Hasri, Nor Hazirah (2018)
In recent years, the Klang Valley area has seen a significant increase of local and international tourists along with increased demand for Islamic tourism hospitality. Although there has been a tremendous growth in hospitality services, the lack of Halal concept best practice for food space design in Klang Valley is a concern that needs to be addressed in this study. In addition, there are some misunderstandings among the public regarding Halal food spaces, as well as the lack of clear design identity of the Halal food spaces in the existing guidelines. Thus, this research aims to establish the design requirements for the concept of Halal food spaces to be used by food and beverages (F&B) operators located in the Klang Valley. The thesis integrates the Halal approach towards a better understanding of the elements and procedures needed for Halal food spaces spatial design. The objectives are i) to analyse the public's understanding on Halal food service establishments, ii) to identify the design requirements of Halal food spaces, and iii) to propose the Halal concept design best practices for food spaces. The research is based on a mixed method methodology. Quantitative data collection is employed to study the depth of perceptions among the public, which applied a convenience sampling. Meanwhile, the qualitative method is used on a purposive sampling to study the Halal concept design compliance based on experts' feedback. A combination of data collection methods was employed according to phases, namely typology study, preliminary study using a questionnaire survey and site observation, pilot testing, actual questionnaire survey, and expert interview sessions. The literature review conducted was based on i) past studies associated with food spaces background, ii) the Halal concept towards F&B from the perspective of the Al-Quran, Hadith and Narration, and Fatwas, and iii) relevant policies, guidelines and Acts. The survey results identified that the degree of awareness among respondents towards the concept of Halal food spaces was satisfactory. The interviews with experts validated the survey findings and existing design practices used for sharing Halal food spaces which are divided into two categories; i) Halal sharing with non-Halal (pork and alcohol type), and ii) Halal sharing with non-Halal ('pork free' and alcohol). Therefore, these findings have led to the formulation of a proposed framework for the design, operation, management, and layout specifications of Halal food spaces known as Best Practice for Halal Concept Food Space (BPHFS). Hence, this research demonstrates the potential of professional appearance on design as a guideline to educate the community for better sustainable development of current practices used in Halal food spaces in Malaysia.